2015
DOI: 10.1016/j.heares.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Shank1 has minimal effects on the molecular composition and function of glutamatergic afferent postsynapses in the mouse inner ear

Abstract: Shank proteins (1–3) are considered the master organizers of glutamatergic postsynaptic densities in the central nervous system, and the genetic deletion of either Shank1, 2, or 3 results in altered composition, form, and strength of glutamatergic postsynapses. To investigate the contribution of Shank proteins to glutamatergic afferent synapses of the inner ear and especially cochlea, we used immunofluorescence and quantitative real time PCR to determine the expression of Shank1, 2, and 3 in the cochlea. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
(72 reference statements)
3
21
0
Order By: Relevance
“…One could argue that via deletion of Shank1 an auditory deficit might be causing the Shank1 −/− pups uttering fewer USV, since Braude et al [] found evidence for expression of Shank1 , but not Shank2 and Shank3 , in the cochlea. However, they did not detect any differences in auditory brainstem responses.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that via deletion of Shank1 an auditory deficit might be causing the Shank1 −/− pups uttering fewer USV, since Braude et al [] found evidence for expression of Shank1 , but not Shank2 and Shank3 , in the cochlea. However, they did not detect any differences in auditory brainstem responses.…”
Section: Discussionmentioning
confidence: 99%
“…All quantitative image analysis was performed on the raw image stacks, without deconvolution, filtering, or gamma correction. The number of synaptic elements per IHC were determined from 3D reconstructions generated using Imaris 6.4 software (Bitplane) as described previously 72 . Final figures were assembled using Adobe PhotoShop and Illustrator software (Adobe Systems).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain cochleae, animals were deeply anesthetized by either isoflurane inhalation (University of Groningen and University of Illinois at Chicago) or injection of a lethal dose of pentobarbital (University of Oldenburg) and then rapidly decapitated. Procedures published previously were used to isolate intact organs of Corti from cochleae for immunofluorescence (Braude et al, ; McLean, Smith, Glowatzki, & Pyott, ). To prevent differences in antigen detection due to differences in processing, identical fixation and immunostaining conditions were used for all specimens.…”
Section: Methodsmentioning
confidence: 99%